2002
DOI: 10.1016/s0010-9452(08)70646-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ‘Masking’ on Picture Naming

Abstract: It is frequently assumed that because compared to nonliving things, living things are less familiar, have lower name frequency, and are more visually complex, this makes them more difficult to name by patients and normal subjects. This has also been implicitly accepted as an explanation for the greater incidence of living thing disorders. Patient studies do not, however, typically contain any premorbid data and so, we do not know that the same variables would have necessarily predicted their 'normal' performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The presence of a considerable category effect in neurologically normal participants may well have been "hidden" by ceiling effects in the control data of previous studies. Indeed, the presence of a normal category advantage (whether living or nonliving) accords with recent findings in healthy participants (Brousseau & Buchanan, 2004;Coppens & Frisinger, 2005;Filliter, McMullen, & Westwood, 2004;Låg, 2005;Låg, Hveem, Ruud, & Laeng, 2006;Laws, 1999Laws, , 2000Laws & Hunter, 2006;Laws & Neve, 1999;Laws, Leeson, & Gale, 2002b;Lloyd-Jones & Luckhurst, 2002;McKenna & Parry, 1994). With the recent accumulation of studies documenting category effects in healthy participants, it is pertinent to ask whether, and indeed how, extant models of category specificity incorporate the notion of category effects in the healthy brain.…”
Section: Discussionmentioning
confidence: 63%
“…The presence of a considerable category effect in neurologically normal participants may well have been "hidden" by ceiling effects in the control data of previous studies. Indeed, the presence of a normal category advantage (whether living or nonliving) accords with recent findings in healthy participants (Brousseau & Buchanan, 2004;Coppens & Frisinger, 2005;Filliter, McMullen, & Westwood, 2004;Låg, 2005;Låg, Hveem, Ruud, & Laeng, 2006;Laws, 1999Laws, , 2000Laws & Hunter, 2006;Laws & Neve, 1999;Laws, Leeson, & Gale, 2002b;Lloyd-Jones & Luckhurst, 2002;McKenna & Parry, 1994). With the recent accumulation of studies documenting category effects in healthy participants, it is pertinent to ask whether, and indeed how, extant models of category specificity incorporate the notion of category effects in the healthy brain.…”
Section: Discussionmentioning
confidence: 63%
“…Finally, previous research has shown that normal and patient populations name pictures of living objects more quickly and accurately than pictures of nonliving objects (e.g., Kiefer, 2001;Laws, Leeson, & Gale, 2002;Takarae & Levin, 2001). For words with high neighborhood frequency there were 11 objects of organic origin (deer, foot, goat, hive, leg, log, nose, pear, run, seal, and sheep) and 16 inorganic objects (bib, bike, book, bus, cage, cake, cape, chair, comb, cone, cup, fan, kite, knife, pan, pen).…”
Section: Methodsmentioning
confidence: 90%
“…This is a parallel effort in English, Italian, Spanish, and Chinese, part of the continuing project "Cross-Linguistic Studies of Aphasia." In this regard, we are particularly interested in studies showing that the kinds of naming errors produced by aphasic patients can also be elicited in normal adults forced to name pictures under perceptual degradation (Laws, Leeson, & Gale, 2002) or under increasing time pressure (Vitkovitch & Humphreys, 1991;Vitkovitch, Humphreys, & Lloyd-Jones, 1993). In the present study, the partici-pants were asked to name the stimuli as fast as possible without making mistakes, and parameters were set to avoid inducing a speed/accuracy trade-off.…”
Section: Summary and Future Directionsmentioning
confidence: 99%